Enhanced thermoelectric properties by effective decoupling of electrical, thermal properties and seebeck coefficient through the addition of rare earth sesquioxides in p-type BiSbTe alloys. (February 2019) - Madavali, Babu; Shin, Dong-won; Kim, Dong-Soo; Hong, Soon-Jik
Abstract: The decoupling between the electrical conductivity and thermal conductivity is a crucial challenge to elevate the figure of merit of a given thermoelectric material. In this research, thermoelectric properties of the rare-earths sesquioxides added Bi-Sb-Te material has been investigated systematically. The electrical conductivity ( σ ) is increased by increase in carrier concentration due to progressive movement of reduced Fermi level deeper into the valance band. Meanwhile, an effective mass of the rare earth added BiSbTe composites has been increased and contributed to the resonant distortion in density of states (DOS), that gives rises to the enhancement of Seebeck coefficient ( α ). Owing to the increment of both factors ( σ & α ), a considerable enhancement in power factor of 14% was achieved for the 2 wt% added BiSbTe/( x -wt%) Nd2 O3 composites. The low content addition of rare earth oxide particles are potentially acts as scattering centers for mid to long wavelength phonons and reduced the thermal conductivity by 7%. The effective decoupling of the electrical and thermal properties by rare earths sesquioxides (Nd2 O3 ) provides a 15% enhancement in thermoelectric figure of merit, ZT for 2 wt% added BiSbTe/( x -wt%)Nd2 O3 composites. Highlights: Coupling between electrical& thermal conductivity, Seebeck coefficient are broken. Electrical conductivity is raised by alteration of Fermi level by rare-earth doping. Rare-earth in BSbTe causes resonant distortion in density of states (DOS). Dispersed rare-earth particles acts as scattering centers and reduced κ values. Dispersion of rare earths sesquioxides in BSbTe provides a 15% enhancement in ZT.